2022
DOI: 10.1002/cctc.202101848
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Binary and Ternary CuZnAl Catalysts without Additives for Efficient CO Hydrogenation to Ethanol

Abstract: Synthesis of ethanol from syngas on CuZnAl catalyst without additives has attracted substantial interest. However, the active sites and the reaction mechanism are still not fully understood due to the complexity of the ternary system. Herein, a series of binary (CuZn, CuAl, ZnAl) and ternary CuZnAl catalysts were prepared using complete liquid method for CO hydrogenation to ethanol. The results show that CAT-CZ and CAT-ZA possess much higher ability for ethanol synthesis than CAT-CA, which is attributed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The XPS O 1s spectra of various catalysts are presented in Figure a. After a rigorous deconvolution of the spectra, three peaks can be identified: (1) the peak with the lowest binding energy (530.3 eV, O L ) is ascribed to lattice oxygen of ZnO; (2) the peak at 531.4 eV relates to oxygen species adsorbed on oxygen vacancies (531.4 eV, O V ); (3) the peak with the highest binding energy corresponds to chemisorption oxygen species (532.3 eV, O C ) at the surface, such as carbonate, adsorbed water, or hydroxyl. , The concentration of oxygen vacancies (O v ) can be quantitatively calculated by S Ov /( S OL + S Ov + S Oc ). As shown in Figure a and Table , the densities of surface O v rank in the following order: Cu/ZnO–5Al > Cu/ZnO–3Al > Cu/ZnO–1Al > Cu/ZnO + 3Al > Cu/ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…The XPS O 1s spectra of various catalysts are presented in Figure a. After a rigorous deconvolution of the spectra, three peaks can be identified: (1) the peak with the lowest binding energy (530.3 eV, O L ) is ascribed to lattice oxygen of ZnO; (2) the peak at 531.4 eV relates to oxygen species adsorbed on oxygen vacancies (531.4 eV, O V ); (3) the peak with the highest binding energy corresponds to chemisorption oxygen species (532.3 eV, O C ) at the surface, such as carbonate, adsorbed water, or hydroxyl. , The concentration of oxygen vacancies (O v ) can be quantitatively calculated by S Ov /( S OL + S Ov + S Oc ). As shown in Figure a and Table , the densities of surface O v rank in the following order: Cu/ZnO–5Al > Cu/ZnO–3Al > Cu/ZnO–1Al > Cu/ZnO + 3Al > Cu/ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…Syngas, which is produced from natural (shale) gas, carbon dioxide, biomass, coal, and carbon-containing waste, can be used to synthesize ethanol. Therefore, syngas-to-ethanol is one of the green routes using nonpetroleum carbon resources to replace dwindling crude oil sustainably. Two pathways, namely, indirect synthesis of ethanol (ISE) and direct synthesis of ethanol (DSE), have been developed for syngas-to-ethanol. Compared with the ISE process involving multiple catalytic steps, DSE is more promising due to its lower energy consumption and higher transformation efficiency . Although DSE has attracted increasing attention in academic and industrial fields, it has not yet been commercialized …”
Section: Introductionmentioning
confidence: 99%
“…In the realm of DSE from syngas, many studies have concentrated on a Rh-based catalyst due to its intriguing preferential ethanol selectivity compared with other materials, such as Mo-based, modified Fischer–Tropsch, and methanol synthesis catalysts. The usual strategies adopted by scientists are the following two aspects: (1) incorporating promoters, such as Fe, Co, Mn, and Li; (2) adjusting the molar ratio of Rh + and Rh 0 via improving the strong metal–support interaction. Although some great improvements have been achieved, DSE over a Rh-based catalyst still needs to enhance the ethanol yield and reduce the undesired byproducts simultaneously. Perovskite oxides (ABO 3 ) are often chosen as the catalyst precursor for the DSE reaction with the following remarkable merits: (1) the elements in perovskite oxides are homogeneously distributed at the atomic scale; , (2) the active sites derived from the precursor can deliver higher dispersion due to the strong interaction between the metal and support .…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of ethanol was about 17%, accounting for 57.18% in total alcohol, and the conversion rate of CO was 10.87%. The results showed that the Zn component in the catalyst played an important role, mainly by forming a high activity CuZnO interface site or a CuZn surface alloy . This paper uses an alternate approach to create a CuZnAl catalyst and studies the performance of its CO hydrogenation on a fixed bed reactor to determine whether this outcome is caused by the catalyst manufacturing method and the slurry bed reactor.…”
Section: Introductionmentioning
confidence: 99%